Effects of telephone health mentoring in community-recruited chronic obstructive pulmonary disease on self-management capacity, quality of life and psychological morbidity: a randomised controlled trial. Issue 9 (6th September 2013) - Walters, Julia; Cameron-Tucker, Helen; Wills, Karen; Schüz, Natalie; Scott, Jenn; Robinson, Andrew; Nelson, Mark; Turner, Paul; Wood-Baker, Richard; Walters, E Haydn
Abstract : Objectives: To assess benefits of telephone-delivered health mentoring in community-based chronic obstructive pulmonary disease (COPD). Design: Cluster randomised controlled trial. Setting: Tasmanian general practices: capital city (11), large rural (3), medium rural (1) and small rural (16). Participants: Patients were invited (1207) from general practitioner (GP) databases with COPD diagnosis and/or tiotropium prescription, response rate 49% (586), refused (176) and excluded (criteria: smoking history or previous study, 68). Spirometry testing (342) confirmed moderate or severe COPD in 182 (53%) patients. Randomisation: By random numbers code, block stratified on location, allocation by sequentially numbered, opaque and sealed envelopes. Intervention: Health mentor (HM) group received regular calls to manage illness issues and health behaviours from trained community health nurses using negotiated goal setting: problem solving, decision-making and action planning. Control: usual care (UC) group received GP care plus non-interventional brief phone calls. Outcomes: Measured at 0, 6 and 12 months, the Short Form 36 (SF-36) and St George's Respiratory Questionnaire (SGRQ, primary); Partners In Health (PIH) Scale for self-management capacity, Hospital Anxiety and Depression Scale (HADS), Center for Epidemiologic Studies-Depression (CES-D) questionnaire, Post-Traumatic Stress Disorder Checklist, Satisfaction with life and hospital admissions (secondary). Results: 182 participants with COPD (age 68±8 years, 62% moderate COPD and 53% men) were randomised (HM=90 and UC=92). Mixed model regression analysis accounting for clustering, adjusting for age, gender, smoking status and airflow limitation assessed efficacy (regression coefficient, β, reported per 6-month visit). There was no difference in quality of life between groups, but self-management capacity increased in the HM group (PIH overall 0.15, 95% CI 0.03 to 0.29; knowledge domain 0.25, 95% CI 0.00 to 0.50). Anxiety decreased in both groups (HADS A 0.35; 95% CI −0.65 to −0.04) and coping capacity improved (PIH coping 0.15; 95% CI 0.04 to 0.26). Conclusions: Health mentoring improved self-management capacity but not quality of life compared to regular phone contact, which itself had positive effects where decline is generally expected.